Seni Teater: Workshop Penyutradaraan di Sanggar Teater Odop SMA 6 Mataram - Renda, Rapi; Hidayat, Irfan; Suryadmaja, Galih; Mawardi, Taufik; Biagi, I Wayan Kusuma Di (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2025)
Directing is a very important pragment in the creative process of theater performances without a director a group will have difficulty in questioning its existence. Odop Theater as a student theater group experiences a lack of directors and regeneration in its community. With this directing training, it is hoped that directors will begin to be regenerated. The training used the methods of 1) experience-based approach, 2) discussion or delivery of directing material, 3) technical training, and 4) performance. The results of the training found that there is potential in students to become a director as evidenced by the results of the training one of the participants managed to create a performance. The performance was staged at the Student Theater Week 2025 competition at Taman Budaya Nusa Teanggara Barat. With the presence of a director in the Odop theater of SMA 6 Mataram, it is hoped that its existence as a theater continues to develop and revive creativity in the studio.